The association of the IL-1ß-31 polymorphism and the development of neuroinfections - Biesiada, Grażyna; Czepiel, Jacek; Piątek, Anna; Birczyńska, Malwina; Żurańska, Justyna; Wołkow, Paweł; Perucki, William; Jędrychowski, Michał; Garlicki, Aleskander (Journal of medical science, 2016)
Introduction. Inflammation of the meninges can have various clinical courses, from mild, self-limiting in some viral neuroinfections to severe, sometimes ending in death. The pro-inflammatory cascade and defects in the inhibitors of the inflammatory response play an important prognostic role. Single nucleotide polymorphisms (SNPs) of the genes encoding cytokines, influence the severity of the inflammatory response.Aim. The aim of this study was to evaluate the effect of selected polymorphisms of proinflammatory cytokines IL-1ß, TNF-? and IL-8 on the development of neuroinfections.Material and Methods. We evaluated the laboratory results of 30 patients treated for bacterial and viral meningitis and compared those to 30 healthy volunteers. The following 4 variants were analyzed for occurrence of genetic polymorphism in patients with meningitis versus the control group: IL-1ß 3953, IL-1ß -31, TNF-? -308, and IL-8 781. Then, we assessed the association between these genetic polymorphisms and the inflammatory response during the course of meningitis.Results and Conclusions. We observed that polymorphism of the IL-1ß-31 significantly differs between patients and healthy subjects, the IL-1ß -31AA polymorphism existed only in healthy individuals (p < 0.001). The WBC count was dependent on the TNF-? -308 polymorphism with a statistically significant difference (p = 0.021) occurring among persons with variants AA and AG. In conclusion the study showed that the presence of the AA genotype of IL-1ß-31polymorphism may have a protective effect on the development of meningitis. This polymorphism was not observed in any patient with meningitis.